PENGATURAN PELANGGARAN BERLALU LINTAS YANG DILAKUKAN OLEH GENERASI MUDA - Pratiwi, Agustina Ni Made Ayu Darma; Saraswati, Putu Sekarwangi; Susrama, I Nengah; Dananjaya, I Gusti Agung Oka; Yogi Widiani P. HS, Ni Luh Gd. Pt. (Kerta Dyatmika, 2025)
Traffic violations have become an increasingly worrying problem for society. Actions such as violating traffic signals, driving a vehicle at an inappropriate speed, or ignoring other driving safety rules can be dangerous for public safety. This research focuses on the younger generation who commit many violations on the highway. There are still many young people who are not yet old enough and do not have a driver’s license, and are already driving motorbikes. The younger generation believes they are mature enough to ride a motorbike, but they don’t know much about driving, which often leads to fatal accidents. This research uses a type of normative legal research to explain the regulation of traffic violations committed by the younger generation. Indonesian criminal law still provides a leniency in imposing the threat of punishment if the perpetrator of the crime is under 18 years of age or has never been married, namely based on the Law. Number 11 of 2012 concerning the Juvenile Criminal Justice System.